Recognition of potential beneficial fungi associated with chontaduro (bactris gasipaes h.b.k.) rhizosphere in the pacific region of valle del cauca, colombia (2011)
The peach palm or chontaduro (Bactris gasipaes H.B.K.) is the principal crop of the rainforest agroecosytems of the Colombian Pacific coast. This region is poorly referenced in the scientific literature despite its high biodiversity and agroecological importance. The aim of this study was to isolate and identify up to the level of genus, fungi from the rhizosphere of B. gasipaes in two areas with different crop management, Citronela and Sabanetas, both in Valle del Cauca. Roots and rhizospherical soil were sampled at three times of varying rainfall from 2006 to 2007. It is hypothesized that the size and diversity of the fungi population are negatively influenced by rainfall, as this is the dominant climatic variable in the study region. Results showed that in Citronela fungi populations were stable during the first two sampling, independent of rainfall between the sampling dates. In Sabaletas, rainfall was higher than in Citronela, which was associated with anaerobic conditions in the rhizosphere that limited fungal growth. The third sampling had higher fungal populations and diversity of fungal genera at both sites which coincides with the period of high rainfall and palm fruit production, conditions that favor the release of exudates from the roots. These factors could have favored secretion of root exudates which in turn, could favor the growth of beneficial microorganisms in the rhizosphere. The genera of fungi isolated were: Trichoderma in both sites, Fusarium and Rhizopus in Citronela only, and Penicillium y Thielaviopsis in Sabaletas only. These fungi could be beneficial and useful in programs of integrated pest management for palm peach production. Thus, the results could serve as a base for future studies in the Pacific region.